Response to fluid challenge in patients with atrial septal defect. (25th November 2020) - D'Alto, M; Chessa, M; Gaio, G; Santoro, G; Giordano, M; Romeo, E; Argiento, P; Wacker, J; D'Aiello, F; Sarubbi, B; Russo, M.G; Naeije, R; et al.
Abstract: Background: A fluid challenge test (FCT) with a rapid infusion of saline allows for discrimination between pre- and post-capillary pulmonary hypertension (PH) and may unmask hidden post-capillary PH. Patients with atrial septal defect (ASD) may develop pre- or post-capillary PH after shunt closure respectively in case of pulmonary vascular disease or left ventricular disease. Aim: To evaluate the haemodynamic changes of the pulmonary circulation in ASD patients undergoing percutaneous closure with indicated according to the current ESC guidelines. Methods: Twenty-three patients (mean age 42.9±12.4 years; 15 female) underwent right heart catheterization in basal conditions and after FCT (volume loading with rapid saline infusion of 7 ml/kg in 10 min) before percutaneous closure of the ASD. Right atrial pressure (RAP), systolic, mean and diastolic pulmonary arterial pressure (sPAP, mPAP and dPAP), pulmonary arterial wedge pressure (PAWP), cardiac output (CO), pulmonary vascular resistance (PVR), systemic vascular resistance (SVR) and the ratio between pulmonary and systemic flow (QP/QS) were calculated four times: before and after inflating the sizing balloon both at baseline and immediately after FCT (Fig. 1). Results: The patients had an increase in pressures and flows after FCT with open ASD: mPAP (18.7±4.4 vs 16.7±4.6 mmHg, p<0.001), PAWP (11.3±3.1 vs 9.2±3.0 mmHg, p<0.001), QP (12.5±2.3 vs 10.3±2.0 l/min, p<0.001), and QS (6.6±1.4 vs 5.9±1.2 l/min, p<0.001) but RAP remained unchanged (8.7±3.0 vs 8.3±2.4 mmHg, p=0.35). PVR (0.2±0.4 vs 0.8±0.3 Wood Units, p<0.001) and SVR (11.2±3.2 vs 12.5±3.2 Wood Units, p=0.02) decreased, and PVR/SVR (0.06±0.02 vs 0.06±0.3, p=0.25) remained unchanged. QP/QS increased in all patients after FCT (mean±SD: 2.0±0.4 vs 1.8±0.4, p<0.001). During a temporary ASD closure by sizing balloon, the patients had increases of RAP (9.0±2.6 vs 7.6±2.6 mmHg, p<0.001) mPAP (19.5±4.0 vs 17.4±3.7 mmHg, p<0.001), PAWP (13.2±2.1 vs 11.2±2.9 mmHg, p<0.001), and CO (7.7±2.7 vs 6.8±2.3 l/min, p<0.001) after FCT. PVR remained unchanged (0.9±0.4 vs 1.1±0.6, p=0.12) and SVR reduced (9.8±2.7 vs 11.3±2.9, p<0.001) after FCT. Conclusions: None of the reported ASD patients presented with FCT criteria of post-capillary PH (that is a PAWP >18 mmHg). The FCT was associated with an increase in QP/QS suggesting that the patients still had a distensible pulmonary circulation. Further studies are needed to explore the relevance of a FCT in ASD patients, particularly those with higher PVR values. Funding Acknowledgement: Type of funding source: None